2011
DOI: 10.1152/ajpheart.00696.2010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular calcium cycling in catecholaminergic polymorphic ventricular tachycardia: a theoretical investigation

Abstract: Sung RJ, Lo CP, Hsiao PY, Tien HC. Targeting intracellular calcium cycling in catecholaminergic polymorphic ventricular tachycardia: a theoretical investigation. Am J Physiol Heart Circ Physiol 301: H1625-H1638, 2011. First published July 8, 2011 doi:10.1152/ajpheart.00696.2010.-Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a malignant arrhythmogenic disorder linked to mutations in the cardiac ryanodine receptor (RyR2) and calsequestrin, predisposing the young to syncope and cardiac arrest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…25 waves, and subsequently cause DADs and TAs by activating I ti due to electrogenic Na + -Ca 2+ exchange current. 26,27) We found that 30 µm M-TMCA abolished Iso/BayK-induced eADs and significantly reduced the occurrence of DADs and TAs (Fig. 4).…”
Section: Resultsmentioning
confidence: 69%
“…25 waves, and subsequently cause DADs and TAs by activating I ti due to electrogenic Na + -Ca 2+ exchange current. 26,27) We found that 30 µm M-TMCA abolished Iso/BayK-induced eADs and significantly reduced the occurrence of DADs and TAs (Fig. 4).…”
Section: Resultsmentioning
confidence: 69%
“…Some patients need to resort to implantable cardioverter/defibrillators, left cardiac sympathetic denervation, and even to cardiac transplantation 24. Based on better understanding of the pathophysiology of CVPT, targeted pharmacotherapy appears to be very promising 43,44. Recently, flecainide therapy has been advocated to be efficacious in suppressing ventricular arrhythmias in CPVT as well as certain ATS patients 20,4547.…”
Section: Altered Intracellular Ca2+ Cycling and Targeted Pharmacothermentioning
confidence: 99%